Pseudomonas fluorescens showing antifungal activity against macrophomina phaseolina, a severe pathogenic fungus of soybean, produces phenazine as the main active metabolite - Castaldi, Stefany (2021)
Fil: Castaldi, Stefany. Università di Napoli Federico II. Dipartimento di Biologia. Complesso Universitario Monte S. Angelo. Via Cintia, Napoli, Italy.